Characterisation of Phytochemicals in Raw and Processed Monodora myristica (Gaertn.) Dunal Seeds by UPLC-MS - Agiriga, Anna N.; Siwela, Muthulisi (Pakistan Journal of Nutrition, 2018)
Background and Objective: Monodora myristica (M. myristica) seeds are processed locally using various indigenous knowledge systems (IKS) based processing techniques like boiling, roasting and frying for varying lengths of time. It is important to determine the effect of these processing methods on its phytochemical constituents, a step necessary in order to explain its nutritional/medicinal use. This paper determined the effects of different cooking methods (boiling and roasting) and cooking times (10, 20 and 30 min) on the phytochemical constituents of M. myristica seeds using ultra performance liquid chromatograph-mass spectrometer (UPLC-MS). Materials and Methods: M. myristica seeds were thermally processed through boiling and roasting for varying lengths of time. Metabolite profiling using UPLC-MS was utilized to identify phytochemicals in raw and processed seeds. Metabolites were characterized by their UV-vis spectra, retention times relative to external standards, mass spectra and comparison to in-house database, phytochemical dictionary of natural products database and reference literature. Results: A total of 32 metabolites were identified, including terpenoids, sterols, alkaloids, fatty acids, saponins, flavonoids, glycosides and coumarins. Processing induced changes in phytochemical composition, more phytochemicals were identified in the roasted samples and the raw (control) sample had the least (four) number of phytochemicals. Conclusion: These findings are promising as they indicate that suitable processing techniques could be established and then applied in the development of new functional foods from whole M. myristica seeds or its extracts. M. myristica seed can be considered a good source of phytochemicals.